GANODERMA APPLANATUM (PERSOON) PATOUILLARD: AS A SOURCE OF ANTICANCER AND ANTIOXIDANT AGENT. - PUSHPA.H; ANAND.M; PANNANGI KASHIMAIAH; PENUGONDA J.V.S.PRADEEP (International Journal of Pharma and Bio Sciences, 2014)
The aim of the present study was to evaluate antioxidant and antitumor activities of Ganoderma applanatum. The methanolic extract of basidiocarps and mycelium of Ganoderma applanatum was analyzed. Antioxidant activity of methanolic extract of basidiocarp and mycelium was characterized using 1, 1,-diphenyl-2- picrylhydrazyl (DPPH) radical scavenging assay. The EC50 of basidiocarp and mycelial mat of G.applanatum was found to be 0.67 mg/ml and 1.50 mg/ml respectively. Anticancer activity of methanolic extracts of mushrooms was determined through MTT (Tetrazolium) assay against three different cell lines, all the extract showed activity on the cell lines. This study reveals that not only basidiocarps of mushroom also vegetative mycelium from the pure culture of G.applanatum has potential anticancer and antioxidant activity, hence this mushroom can be exploited for its useful metabolites in food and pharmaceutical industries.